Research of defects of hot-rolled steel having rolling nature of formation of the rolling shop no. 1 of rolling mill 850 at OJSC «BSW – Management Company of Holding «BMC» - I. A. Kovaleva; Yu. A. Potapenko (Литьë и металлургия, 2019)
Rolling is the final stage of the metallurgical cycle and has a great influence on the quantity and quality of products, as well as on various technological and economic indicators of the plant.The OJSC « BSW – Management Company of Holding «BMC» is working on the development and supply of hot-rolled round products for the automotive industry in Western Europe.The increasing requirements for the quality of the surface of hot-rolled steel are a powerful incentive to improve the technology of its production, which is impossible without the use of modern methods of control and proper identification of detected defects.The article presents the results of the study of defects of hot-rolled products of rolling mill № 1 850, having the rolling nature of formation.Metallographic study was conducted on the basis of: visual inspection of defects, in some cases with the preparation of a template for the study of macrostructure and location of defects; analysis of images of the microstructure of the cross section of the sample in the area of defects. With the help of characteristic external and microstructural features of defects, special etching in reagents, the causes of their formation were established, and recommendations for their minimization or complete elimination were proposed.